Correction to: 4-Chloro-3-nitro-N-butylbenzenesulfonamide acts on KV3.1 channels by an open-channel blocker mechanism (Amino Acids, (2018), 10.1007/s00726-017-2488-0) - Bassetto Junior, Carlos Alberto Zanutto [UNESP]; Varanda, Wamberto Antonio; González, Eduardo René Pérez [UNESP] (Springer Nature, 2018)
Unfortunately, grey trace on Figure 2c was missing in the original publication of the article.